2022
DOI: 10.3389/fimmu.2022.847617
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Immunoinformatic Analysis to Predict Candidate T-Cell Epitopes for SARS-CoV-2 Vaccine Design

Abstract: Since the first outbreak of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 2019, its high infectivity led to its prevalence around the world in an exceptionally short time. Efforts have been made to control the ongoing outbreak, and among them, vaccine developments are going on high priority. New clinical trials add to growing evidence that vaccines from many countries were highly effective at preventing SARS-CoV-2 virus infection. One of them is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Here, it is worth mentioning that different mutations in positions such as N501, K444, G446, S477 and N439 are reported to enhance the affinity of these residues towards the binding of human ACE2 receptor [26,40]. In accordance with our study, a few recently published articles also documented the promising role of spike protein and T-cell-based epitopes in vaccine design for COVID-19 infection [41,42]. A recently published article by Zannella et al, 2022, showed that synthesized peptides from the selected nucleotide sequences of the genome of coronaviruses were not found to be toxic to the cultured cells and also had resistant properties against serum proteases.…”
Section: Discussionsupporting
confidence: 89%
“…Here, it is worth mentioning that different mutations in positions such as N501, K444, G446, S477 and N439 are reported to enhance the affinity of these residues towards the binding of human ACE2 receptor [26,40]. In accordance with our study, a few recently published articles also documented the promising role of spike protein and T-cell-based epitopes in vaccine design for COVID-19 infection [41,42]. A recently published article by Zannella et al, 2022, showed that synthesized peptides from the selected nucleotide sequences of the genome of coronaviruses were not found to be toxic to the cultured cells and also had resistant properties against serum proteases.…”
Section: Discussionsupporting
confidence: 89%